Metode Brainstorming dan Media Audiovisual Dalam Upaya Mengedukasi Kader Untuk Secara Mandiri Mengenali dan Mengelola Stunting di Desa Larike Kabupaten Maluku Tengah - Khartini Kaluku; Martha Puspita Sari; Santi Aprilian Lestaluhu (Universitas Lancang Kuning, 2021)
Stunting is a condition when a person's height is known to be shorter when compared to someone else's age. Stunting rate in Indonesia is high, straight line with poor nutrition. The purpose of this community service is to increase knowledge of stunting through health counseling methods and handle independently through cadre assistance. This method begins with brainstorming and Focus Group Discussion (FGD) followed by training, distribution of leaflets, and screening of video stunting to Posyandu cadres accompanied by nutrition assistance as much as 3x visits in the context of independent handling of stunting for toddlers. The results obtained that there is an increase in knowledge after brainstorming and playback of audiovisual media through counseling using these media using the Wilcoxon test with a p-value of 0.00. The conclusion is that the method of brainstorming and audiovisual media is an effective media as an alternative to educating cadres and being able to recognize and manage stunting independently.